2015
DOI: 10.1007/s10531-015-0980-y
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic Forest spontaneous regeneration at landscape scale

Abstract: The Atlantic Forest suffered five centuries of continuous deforestation related to successive economic cycles, and is now reduced to 11.7 % of its original cover. The Atlantic Forest Restoration Pact was launched in 2009 and aims to restore 15 million hectares until 2050. Natural regeneration can play an important role in meeting this target, however little attention has been paid to this process and there is a gap in the knowledge about its driving factors at the landscape scale. We mapped forest cover of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 54 publications
6
86
0
7
Order By: Relevance
“…Slope, distance to watercourses and distance to forest remnants were decisive factors determining where forest regrowth occurred from 2000 to 2010, corroborating other studies in the Atlantic Forest region (de Rezende, Uezu, Scarano, & Araujo, 2015;Molin et al, 2017;Teixeira, Soares-Filho, Freitas, & Metzger, 2009). With the exception of the Forest landscape unit, where industrial crop production is found, natural regeneration was favoured in previous croplands when slopes were above 10%.…”
Section: Drivers Of Forest Regenerationsupporting
confidence: 87%
“…Slope, distance to watercourses and distance to forest remnants were decisive factors determining where forest regrowth occurred from 2000 to 2010, corroborating other studies in the Atlantic Forest region (de Rezende, Uezu, Scarano, & Araujo, 2015;Molin et al, 2017;Teixeira, Soares-Filho, Freitas, & Metzger, 2009). With the exception of the Forest landscape unit, where industrial crop production is found, natural regeneration was favoured in previous croplands when slopes were above 10%.…”
Section: Drivers Of Forest Regenerationsupporting
confidence: 87%
“…Finally, it is important to note that 63% of the courses mention natural regeneration as an ecological restoration technique. Recently, several studies have shown the potential of natural regeneration for large-scale restoration (Rezende et al 2015;Chazdon & Uriarte 2016;Strassburg et al 2016). Therefore, multiple ecological restoration technique options must be considered for different local scenarios (ecological, social, and economic;Holl & Aide 2011;Brancalion et al 2016b).…”
Section: Monmentioning
confidence: 99%
“…A orografia da região influencia também na variabilidade climática, com predomínio de clima subquente, com temperaturas médias que variam entre 13,8ºC e 24,3ºC (NIMER, 1989) e elevados índices pluviométricos, que atingem um total anual próximo a 2.500 mm nas áreas mais altas, diminuindo progressivamente para o norte até alcançar 1.300 mm (CANEDO; EHRLICH; LACERDA, 2011). Os terrenos íngremes, elevados e consequentemente pouco acessíveis facilitaram a manutenção da cobertura florestal em cerca de 60% do município (FRANCISCO; ALMEIDA, 2012), incluindo florestas secundárias em diferentes estágios de sucessão, sujeitas à exploração seletiva ou regeneradas após o abandono de áreas agrícolas e pastagens devido à baixa fertilidade dos solos, erosão, alta umidade, diminuição da população rural, mudanças na legislação e fiscalização ambiental, e à criação de unidades de conservação (CASTRO, 2015;REZENDE et al, 2015). A área pertence ao Bioma Mata Atlântica e tem como formação vegetal dominante a Floresta Ombrófila Densa Montana (VELOSO; RANGEL FILHO; LIMA, 1991), sendo considerada como de alta prioridade para a conservação de espécies vegetais e animais (GUEDES-BRUNI; LIMA, 1997;ROCHA et al, 2009).…”
Section: áRea De Estudounclassified